Transformation of Post-Authoritarian Rural Development in Indonesia: A Study of Farmer Breeder Community Development in West Bandung Regency - Rifandini, Rahmalia (Masyarakat: Jurnal Sosiologi, 2018)
The idea of post-authoritarian rural development is seen as the transformation of rural development since it no longer places the village as an object of development characterized by the demand for the preparation of rural development instruments. However, in practice, the development instruments do not result in the improvement of agricultural and livestock productivity as it happened in Kampung Pasir Angling, Suntenjaya Village, West Bandung Regency, West Java. Using a critical development perspective, the study argues that rural development transformation may apply if not limited to changes in public policy strategies, but rather to the social change in various sectors of rural life. This article argues that the transformation of rural development—which has the characteristics of empowerment — can be achieved when there is a placement of the civil society element as the party that initiates the articulation of needs and activates the consciousness of farmer-breeders in the practice of rural development. This article was written based on a qualitative research in describing the community development of farmer-breeders in Kampung Pasir Angling, Suntenjaya Village, West Bandung Regency, West Java.